Methodology for Determining the Halal of Medicinal and Food Products in Maslahah Perspective - Muhammad Nusran; Abdul Muher; Sitnah A. Marasabessy; Nurlaila Abdullah (UPT Pusat Studi Aswaja UNISNU Jepara, 2021)
AbstractMedicine and food are the two primary commodities needed for humans. Both are very important for maintaining human survival and also the environment. With the rapid development of science and technology (saintec), including the production of food and medicine, there have been many product innovations that utilize natural resources optimally or reprocess existing resources. It is undeniable that advances in science and technology are able to produce various products that not only make optimal use of resources, but are able to answer the various human needs for medicine and food. With the obligation, especially Muslim consumers, to only consume Halal medicines and foods, problems arise related to the halal status of medicinal and food products. Even though there have been many writings from scholars regarding the methodology of stipulating halal law or the prohibition of something, it will be, but with the phenomenon of the very wide variety of medicinal and food industry products, this methodology is still very important to be reviewed again. The aim of this paper is to produce a specific methodology for the determination of halal medicinal and food products from a Maslahah perspective. This paper is a literature study using an analysis of the istimbath process using the Maslahah perspective on medicinal and food products.The results of this study are a methodology that canbe used as a basis for determining the halalness of medicinal and food products from the Maslahah perspective as well as practical instructions for non-Sharia communities to assess whether a product is Halal or not.Keywords: Halal, medicine, food, istimbath, maslahah, methodology